Effects of Physician Experience, Specialty Training, and Self-referral on Inappropriate Diagnostic Imaging - Young, Gary J. (J Gen Intern Med, 2020)
BACKGROUND: Although previous research has demonstrated high rates of inappropriate diagnostic imaging, the potential influence of several physician-level characteristics is not well established. OBJECTIVE: To examine the influence of three types of physician characteristics on inappropriate imaging: experience, specialty training, and self-referral. DESIGN: A retrospective analysis of over 70,000 MRI claims submitted for commercially insured individuals. Physician characteristics were identified through a combination of administrative records and primary data collection. Multi-level modeling was used to assess relationships between physician characteristics and inappropriate MRIs. SETTING: Massachusetts PARTICIPANTS: Commercially insured individuals who received an MRI between 2010 and 2013 for one of three conditions: low back pain, knee pain, and shoulder pain. MEASUREMENTS: Guidelines from the American College of Radiology were used to classify MRI referrals as appropriate/inappropriate. Experience was measured from the date of medical school graduation. Specialty training comprised three principal groups: general internal medicine, family medicine, and orthopedics. Two forms of self-referral were examined: (a) the same physician who ordered the procedure also performed it, and (b) the physicians who ordered and performed the procedure were members of the same group practice and the procedure was performed outside the hospital setting. RESULTS: Approximately 23% of claims were classified as inappropriate. Physicians with 10 or less years of experience had significantly higher odds of ordering inappropriate MRIs. Primary care physicians were almost twice as likely to order an inappropriate MRI as orthopedists. Self-referral was not associated with higher rates of inappropriate MRIs. LIMITATIONS: Classification of MRIs was conducted with claims data. Not all self-referred MRIs could be detected. CONCLUSIONS: Inappropriate imaging continues to be a driver of wasteful health care spending. Both physician experience and specialty training were highly associated with inappropriate imaging.